RUMAH ADAT SUKU ALOR BESAR SEBAGAI REPRESENTASI IDENTITAS BUDAYA DAN WARISAN LELUHUR DESA ALOR BESAR KECAMATAN ALOR BARAT LAUT - Yona Teiko; Yumni S. Wabang, Halena Muna Bekata, Petrus Mau Telu Doni, Martha Karfing, Welmince Maiateng, Yadra (Adiba Aisha Amira, 2025)
This study aims to examine the Alor Besar traditional house as a representation of cultural identity that reflects the traditional life and beliefs of the Alor Besar community. Researchers used a qualitative research method with a degangan ethnogaphy approach using interview techniques and direct observation at the location of the traditional house. The Alor Besar traditional house is a symbol of the culture and ancestral heritage of the Alor community, which illustrates the social, spiritual and historical values held firmly by the local community. The results showed that the Alor Besar traditional house not only functions as a place to live, but also as a means of maintaining relationships with ancestors, customs, and as a centre for community social activities. The conclusion of the big aat alor house is very important in maintaining the cultural identity of the big alor community.